ISEV position paper: extracellular vesicle RNA analysis and bioinformatics. - O'DRISCOLL, LORRAINE (My University, 2013)
Extracellular vesicles (EVs) are the collective term for the various vesicles that are released by cells into the extracellular space. Such vesicles include exosomes and microvesicles, which vary by their size and/or protein and genetic cargo. With the discovery that EVs contain genetic material in the form of RNA (evRNA) has come the increased interest in these vesicles for their potential use as sources of disease biomarkers and potential therapeutic agents. Rapid developments in the availability of deep sequencing technologies have enabled the study of EV-related RNA in detail. In October 2012, the International Society for Extracellular Vesicles (ISEV) held a workshop on "evRNA analysis and bioinformatics." Here, we report the conclusions of one of the roundtable discussions where we discussed evRNA analysis technologies and provide some guidelines to researchers in the field to consider when performing such analysis.
PUBLISHED
doi: 10.3402/jev.v2i0.22859 PMID: 24376909
Keywords: bioinformatics; RNA; evRNA; deep sequencing; extracellular vesicles; Cancer; CANCER